A Review of the Implementation Challenges of Public Procurement Reforms Initiatives in Nigeria - Zadawa, Abdullahi Nafiu; Hussin, Abdul Aziz (School of Social Sciences, 2015)
Public Procurement as one of the major functions of government in Nigeria is playing a significant role towards infrastructural development in the country. Reforming the public procurement sector was necessary to regulate the entire procurement process. In an attempt to harmonize the various reform initiatives, Public Procurement Act (hereinafter referred as “PPA”) was passed into law in June 2007. This paper identified and reviewed some major challenges facing the full implementation of the procurement procedural guidelines as highlighted by the Act. These include unfamiliarity, fraudulent practices and influences, and subsequently concludes that, ensuring full implementation required adequate awareness, imposing penalty for defaulters as well as limiting influences of project awards. The establishment of National Council of Public Procurement is one of the vital elements (as provided under section 1 of PPA 2007, but it is yet to be fulfilled).